Efeitos da quebra espontânea da simetria-CPT e da invariância de Lorentz no fenômeno da condensação de Bose-Einstein - Silva, Kleber Anderson Teixeira da (2011)
The Bose-Einstein condensate (BEC), also known as the fifth state of the matter, was predicted theoretically by Albert Einstein in 1925 and verified experimentally 70 years later in 1995. This dissertation addresses the effects of spontaneous broken of the CPT-symmetry and of the invariance Lorentz (also called simply the violation of Lorentz symmetry) in the Bose-Einstein condensation of an ideal bosonic gas in the limits nonrelativistic and will ultrarelativ´ıstico. The work is based on a model of fields theory described by a massive complex scalar field in the framework of spontaneous breaking of the CPT-symmetry and of the Lorentz invariance. First we study the CBE in the nonrelativistic limit starting from the non relativistic version of our model. Thus, the existence of the CBE imposes strong restrictions on some parameters governing the breach of Lorentz invariance (VIL). We observed that only the critical temperature is modified by the VIL. Also, we use experimental data to obtain limits upper for the coefficients that control the VIL. Because of our model describe consistently the CBE in the non relativistic limit We can use it to study the CBE ultrarelativıstica of an ideal bosonic gas loaded. Thus, we show that the construction of a partition function well defined to describe the relativistic ideal gas, imposes strong restrictions on two parameters that control the VIL. The analysis of the CBE in the ultrarelativistico limit shows that both the critical temperature as the chemical potential are affected by the spontaneous breaking of the invariance of Lorentz.